Evaluation of Some Mechanical Properties of Reinforced Acrylic Resin Denture Base Material(An In Vitro Study) - Tarik Kassab Bashi; Luma M Al-Nema (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate the effect of thickness of acrylic denture base resin on the transverse strength, also to evaluate the effect of metal and fiber reinforcements on the fracture resistance of denture base resin by four mechanical tests: Transverse strength; Charpy impact strength; Tensile strength and Rockwell Indentation Hardness. Materials and methods : Heat-cured resin, and three types of reinforcing metals were used which were: The cobalt-chromium alloy mesh, stainless steel wire and nickel alloy plate. Three forms of glass fiber also were used: Random, woven, and aligned unidirectional. The effect of these reinforcing materials on the mechanical properties of heat-cured resin had been evaluated by measuring the transverse strength by the Instron testing machine, tensile strength by the Textile tensile strength Tester, the impact strength by the Charpy type impact Tester and finally the hardness by the Rockwell hardness tester. Three hundred samples were prepared in this study. Results: Revealed a statistically significant effect of thickness on the transverse strength of heat-cured resin. Results also showed that all forms of fiber and metal reinforcements had a significant effect on the transverse strength, tensile strength , impact strength and hardness of denture base resin. Conclusions: The thickness significantly increased the transverse strength of denture base resin. All forms of metal and glass fiber reinforcement significantly improved the transverse strength, impact strength and tensile strength of denture base resin. All forms of metal and fiber reinforcement acted to reduce the hardness of denture base resin